Geografitti : a mapping of handwritten public expression. - Schasse, Aaron; DeGrave, Jeff (My University, 2007)
This project consisted of the collection, documentation, cataloguing and mapping of informal handwritten public expression (a.k.a. graffiti) in Eau Claire, Wisconsin.
Color poster of a map identifying the location of graffiti photographed in the course of the project.
Keywords: Graffiti--Pictorial works--Maps.; Graffiti--Wisconsin--Eau Claire--Maps.; Photographs.; Posters.